2001
DOI: 10.1016/s0005-2728(01)00200-6
|View full text |Cite
|
Sign up to set email alerts
|

The reaction center of green sulfur bacteria1Dedicated to the memory of Jan Amesz.1

Abstract: The composition of the P840-reaction center complex (RC), energy and electron transfer within the RC, as well as its topographical organization and interaction with other components in the membrane of green sulfur bacteria are presented, and compared to the FeS-type reaction centers of Photosystem I and of Heliobacteria. The core of the RC is homodimeric, since pscA is the only gene found in the genome of Chlorobium tepidum which resembles the genes psaA and -B for the heterodimeric core of Photosystem I. Func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(84 citation statements)
references
References 102 publications
2
75
0
Order By: Relevance
“…The RC complex of the green sulfur bacterium Chlorobium tepidum consists of four subunits, PscA, PscB, PscC, and PscD with an antenna size of about 30 bacteriochlorophyll (BChl) molecules, whereas the heterodimeric photosystem I complex is made of 12 polypeptides with a much larger antenna size of nearly 100 chlorophyll (Chl) molecules (4,5). The functions of PscA, PscB, and PscC have been studied intensively using biochemical and spectroscopic methods.…”
mentioning
confidence: 99%
“…The RC complex of the green sulfur bacterium Chlorobium tepidum consists of four subunits, PscA, PscB, PscC, and PscD with an antenna size of about 30 bacteriochlorophyll (BChl) molecules, whereas the heterodimeric photosystem I complex is made of 12 polypeptides with a much larger antenna size of nearly 100 chlorophyll (Chl) molecules (4,5). The functions of PscA, PscB, and PscC have been studied intensively using biochemical and spectroscopic methods.…”
mentioning
confidence: 99%
“…Of the multiple sulfide oxidation electron transport pathways with photooxidized P840 as the terminal electron acceptor in C. tepidum, the one involving SQR appears to be more efficient in terms of energy conversion than the others, because it should generate a proton-motive force through a cyt b-Riesketype iron-sulfur protein complex during the oxidation of sulfide by photooxidized P840, and the others do not. 30) Although the FCSD and SoxF pathways are energetically inefficient as compared with the SQR pathway and the affinities for sulfide did not differ very much, retention of these activities is likely favored under certain environmental conditions, because sulfide is a diffusible substrate required by many bacterial species occupying the same ecological niche. 6) Oxidation of sulfide by FCSD or SoxF, or even by core TOMES to elemental sulfur, allows an individual bacterium to utilize sulfide and subsequently generate six electrons as electron donors for further reactions.…”
Section: Thiosulfatophilummentioning
confidence: 95%
“…29) The primary donor of the reaction center (RC) is a special pair of bacteriochlorophylls called P840, and its immediate electron donor is RC-bound cyt c-551. 30) Itoh et al 31) found that a soluble mono-heme cyt c-554 of about 10 kDa (the CT0075 protein, 10) sometimes called a small soluble cytochrome c) donates electrons to bound cyt c-551 rather than directly to oxidized P840. In the reconstituted core TOMES (SoxAXK, SoxB, SoxYZ) of this bacterium, cyt c-554 functioned as an efficient electron acceptor.…”
mentioning
confidence: 99%
“…Similar results were observed by Frigaard et al (28) for the bchK mutant. The absorption band near 800 nm was derived from a combination of BChl a-binding proteins, including CsmA, Fenna-Matthews-Olson protein, and the reaction centers (28,31,32). Fig.…”
Section: Identification Of Potential Bchl C D and E Biosynthesis Gene-mentioning
confidence: 99%